The Influence of Transformational Leadership and Role Overload on Public Sector Employee Burnout with the Moderation of Human Resources Management Practices - Amanda Putri Pertiwi; Riani Rachmawati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Burnout among public sector employees is an important issue due to the high work demands and pressures in the government environment, which impacts individual well-being and organizational performance. This study examines the effect of transformational leadership (TFL) and role overload on burnout among public sector employees, focusing on the moderating role of human resource management (HRM) practices. Data was collected from 415 employees of Statistics Indonesia (BPS) and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results showed that TFL plays a significant role in reducing burnout by providing vision, motivation, and support to employees. On the other hand, role overload was also identified as an important contributor to increasing employee burnout. In addition, the findings of this study highlight the dark side of excessive HRM that can weaken the positive effects of transformational leadership and have the potential to worsen employee burnout, so a balanced HRM approach that is oriented towards employee well-being is needed. Overall, this study provides insight into the interaction between TFL, role overload, and HRM and offers valuable knowledge for stakeholders related to HRM practices in the public sector.